A Dual Role for the dREAM/MMB Complex in the Regulation of Differentiation-Specific E2F/RB Target Genes - Lee, Hangnoh (American Society for Microbiology, 2012)
E2F and RB proteins regulate the expression of genes involved in cell cycle progression, apoptosis, differentiation, and development. Recent studies indicate that they function as part of an evolutionarily conserved multiprotein complex termed dREAM/DREAM/LINC. Here we characterize the role of the Drosophila complex, dREAM, in the regulation of differentiation-specific E2F target genes in actively proliferating cells. These genes are regulated differently from cell cycle-related E2F targets, they do not depend on E2F activation, and E2F/RB repression is maintained throughout the cell cycle. In proliferating cells, their repression is dependent on dREAM. We find that dREAM plays a dual role in their regulation. First, it is required for the stability of the repressive dE2F2/RBF complexes at their promoters during S phase. Second, we find that dREAM is indispensable for both transcriptional repression mechanisms employed at these genes.